High Phosphate Induces and Klotho Attenuates Kidney Epithelial Senescence and Fibrosis - Maique, Jenny; Flores, Brianna; Shi, Mingjun; Shepard, Sierra; Zhou, Zhiyong; Yan, Shirely; Moe, Orson W.; Hu, Ming Chang (Frontiers in Pharmacology, 2020)
Cellular senescence is an irreversible cell growth arrest and is associated with aging and age-related diseases. High plasma phosphate (Pi) and deficiency of Klotho contribute to aging and kidney fibrosis, a pathological feature in the aging kidney and chronic kidney disease. This study examined the interactive role of Pi and Klotho in kidney senescence and fibrosis. Homozygous Klotho hypomorphic mice had high plasma Pi, undetectable Klotho in plasma and kidney, high senescence with massive collagen accumulation in kidney tubules, and fibrin deposits in peritubular capillaries. To examine the Pi effect on kidney senescence, a high (2%) Pi diet was given to wild-type mice. One-week of high dietary Pi mildly increased plasma Pi, and upregulated kidney p16/p21 expression, but did not significantly decrease Klotho. Two-weeks of high Pi intake led to increase in plasminogen activator inhibitor (PAI)-1, and decrease in kidney Klotho, but still without detectable increase in kidney fibrosis. More prolonged dietary Pi for twelve weeks exacerbated kidney senescence and fibrosis; more so in heterozygous Klotho hypomorphic mice compared to wild-type mice, and in mice with chronic kidney disease (CKD) on high Pi diet compared to CKD mice fed a normal Pi diet. In cultured kidney tubular cells, high Pi directly induced cellular senescence, injury and epithelial-mesenchymal transition, and enhanced H2O2-induced cellular senescence and injury, which were abrogated by Klotho. Fucoidan, a bioactive molecule with multiple biologic functions including senescence inhibition, blunted Pi-induced cellular senescence, oxidation, injury, epithelial-mesenchymal transition, and senescence-associated secretary phenotype. In conclusion, high Pi activates senescence through distinct but interconnected mechanisms: upregulating p16/p21 (early), and elevation of plasminogen activator inhibitor-1 and downregulating of Klotho (late). Klotho may be a promising agent to attenuate senescence and ameliorate age-associated, and Pi-induced kidney degeneration such as kidney fibrosis.